2013
DOI: 10.3389/fphys.2013.00078
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Cardiovascular Response during Electronic Control Device Exposure in Law Enforcement Trainees

Abstract: Objective: Law enforcement represents a large population of workers who may be exposed to electronic control devices (ECDs). Little is known about the potential effect of exposure to these devices on respiration or cardiovascular response during current discharge.Methods: Participants (N = 23) were trainees exposed to 5 s of an ECD (Taser X26®) as a component of training. Trainees were asked to volitionally inhale during exposure. Respiratory recordings involved a continuous waveform recorded throughout the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Durch die körperliche Beanspruchung während einer CEW-Exposition kommt es indirekt zu einem reaktiven Anstieg der Herzfrequenz [33,34] und zu einer Verminderung des systolischen und diastolischen Drucks [35,36]…”
Section: Kardiale Und Adrenerge Wirkungunclassified
See 1 more Smart Citation
“…Durch die körperliche Beanspruchung während einer CEW-Exposition kommt es indirekt zu einem reaktiven Anstieg der Herzfrequenz [33,34] und zu einer Verminderung des systolischen und diastolischen Drucks [35,36]…”
Section: Kardiale Und Adrenerge Wirkungunclassified
“…Die Wirkung einer CEWinduzierten allgemeinen Muskelkontraktion ist somit vergleichbar mit einer mittel-bis höhergradigen körperlichen Anstrengung kombiniert mit einer allgemeinen Stressreaktion [42]. Während einer CEW-Exposition kommt es zu einem primär stressbedingten Anstieg von Katecholaminen und Glukokortikoiden [33,43] sowie zu einem primär physisch reaktiv bedingten verminderten pH-Wert [28,33,34] bei gleichzeitig erhöhtem Laktat [33,44,45] und erhöhter Kreatinkinase [46]. Diese Veränderungen wurden in der wissenschaftlichen Literatur als klinisch nicht relevante, zu…”
Section: Metabolische Und Neuroendokrine Wirkungunclassified
“…In addition, the motivation for subjects to perform certain tasks could be different during research vs. field conditions. VanMeenen et al (172) reported that, during exposure of human subjects to the X26 CEW for 5 sec, voluntary inspiration was severely compromised. Although law-enforcement trainees actively attempted to breathe, most individuals exhibited cessation of breathing ("absence of any orderly tidal breathing").…”
Section: Respirationmentioning
confidence: 99%
“…Potential effects of repeated interruption of normal breathing (even when interspersed with periods of no applications of CEWs) have not been elucidated. VanMeenen et al (172) suggested that a forced breath hold of 30 sec could have major clinical consequences in patients with even moderate respiratory impairment.…”
Section: Respirationmentioning
confidence: 99%
“…There are several types of PU, including the following: liquid PU for hollow-fiber devices, PU for dip-molding, PU coatings, biostable PU and thermoplastic PU [6]. Sivak WN [7] synthesized a novel PU drug delivery system based on lysine diisocyanate and glycerol using various tertiary amines and organometallic urethane as catalysts.…”
Section: Introductionmentioning
confidence: 99%